Menata Kontestasi Simbol-Simbol Keagamaan di Ruang Publik Kota Jayapura - Muhamad Yusuf; Sahudi Sahudi; Marwan Sileuw; Linda Safitri (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
The freedom to use Christian religious symbols in Jayapura City creates social unrest and jealousy for other people. This article aims to analyze the religious symbols used by Christians, intense contestation of religious symbols by Christians in Jayapura City, and ideas about its arrangement. This qualitative research uses the paradigm of social phenomenology. This study found that Muslims in Jayapura City is the second largest after Protestant Christianity, but religious development is ranked third after Protestant Christianity and Catholicism. Islam is considered the religion of migrants. The rise of Christian religious symbols in Jayapura City as holy people who have majority control and have freedom of expression in religious symbols is carried out by religious groups in other areas and applied in Jayapura City. The role of central government policy is needed to emerge various ideas in the community in the region. Regional regulations provide freedom for the use of religious symbols. The religious majority who control the government sector has control over the use of religious symbols rather than minority groups by making rules that bind religious communities and raise the exclusivity of the majority group. The local parliament members (DPRD)'s inability to realize the aspirations of the Muslim community of Jayapura City is due to the lack of Muslim members of the local parliament (DPRD). Hence, they have limited numbers in supervising emerging policies, including the use of religious symbols.